Disorders of Sex Development: A 10 Years Experience with 73 Cases from the Kashmir Valley - Misgar, Raiz Ahmad (Indian J Endocrinol Metab, 2019)
PURPOSE: To present the clinical data, investigative profile, and management of patients with disorders of sex development (DSD) from the endocrine unit of a tertiary care university hospital. MATERIALS AND METHODS: This retrospective study included 73 cases of DSD, evaluated and managed at Department of Endocrinology, Sher-i-Kashmir Institute of Medical Sciences, Srinagar, Kashmir, over a period of 10 years from September 2008 to August 2018. RESULTS: Twenty-nine patients (39.7%) had 46 XY DSD and twenty-nine patients (39.7%) had 46 XX. Sex chromosome DSD was diagnosed in 15 (20.5%) patients. Of 29 patients with 46 XY DSD, 17 (58.6%) had 5α-reductase type-2 deficiency (5α-RD) and 6 (20.7%) had complete androgen insensitivity syndrome. In our patients with 5α-RD, the history of consanguinity was documented in nine (52.9%) patients. Two patients had testosterone biosynthetic defect and one patient had partial androgen insensitivity syndrome. Of 29 patients with 46 XX DSD, 16 (55.1%) had congenital adrenal hyperplasia (CAH). Of 15 patients with sex chromosome DSD, 7 patients had Turner's syndrome, 7 had Klinefelter's syndrome, and 1 patient had mixed gonadal dysgenesis. CONCLUSION: In our study, equal number of patients had 46 XY DSD and 46 XX DSD. We are for the first time reporting from India that the most common cause of 46 XY DSD is 5α-RD, whereas CAH is the most common cause of 46 XX DSD as reported previously.